2015
DOI: 10.1144/sp420.13
|View full text |Cite
|
Sign up to set email alerts
|

Use of a high-precision gravity survey to understand the formation of oceanic crust and the role of melt at the southern Red Sea rift in Afar, Ethiopia

Abstract: Abstract:The Red Sea arm of the triple junction in northeastern Ethiopia provides an opportunity to investigate rift-forming processes at divergent boundaries. In an attempt to study the subsurface, especially the distribution and role of melt in the rifting process, we carried out a high-precision gravity survey with a mean-square error of 0.011 mgal, assisted by differential global positioning system measurements. The profile is 162 km long and strikes ENE-WSW across the southern part of the Red Sea rift at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“…Farther south where the MHR segment merges with the Tendaho Graben, high conductivity is again imaged off axis at lower crustal depths (Johnson et al, ) (Figure ) but with smaller inferred volumes than beneath the recently active northern MHR. This coincides with an inferred partially molten gabbroic body that has been intruded into a thinned lower crust deduced from microgravity data (Lewi et al, ) (cf. models of MT and gravity data through the Boset volcano in the northern MER; Whaler & Hautot, ; Cornwell et al, (), section 4.2).…”
Section: Late Stage Continental Breakup and Initiation Of Seafloor Spsupporting
confidence: 88%
See 1 more Smart Citation
“…Farther south where the MHR segment merges with the Tendaho Graben, high conductivity is again imaged off axis at lower crustal depths (Johnson et al, ) (Figure ) but with smaller inferred volumes than beneath the recently active northern MHR. This coincides with an inferred partially molten gabbroic body that has been intruded into a thinned lower crust deduced from microgravity data (Lewi et al, ) (cf. models of MT and gravity data through the Boset volcano in the northern MER; Whaler & Hautot, ; Cornwell et al, (), section 4.2).…”
Section: Late Stage Continental Breakup and Initiation Of Seafloor Spsupporting
confidence: 88%
“…Active deformation processes in the Afar depression provide important clues (e.g., Keir et al, ; Pagli et al, ). Constraints on crustal structure primarily come from teleseismic receiver function studies (Ayele et al, ; Dugda et al, ; Hammond et al, ; Stuart et al, ), wide‐angle seismic surveys (Berckhemer et al, ; Maguire et al, ; Makris & Ginzburg, ), gravity (Lewi et al, ; Redfield et al, ; Tessema & Antoine, ; Tiberi et al, ), and MT studies (Desissa et al, ; Didana et al, , ; Johnson et al, ; Van Ngoc et al, ). A primary focus is to address the links between crustal thinning, magma intrusion, and subsidence to address a long‐standing debate in plate tectonics: When does seafloor spreading start?…”
Section: Late Stage Continental Breakup and Initiation Of Seafloor Spmentioning
confidence: 99%
“…At the Gademotta caldera, no recent volcanic activity has been reported (Woldegabriel et al, ); therefore, the presence of a cooled igneous body (which would have higher electrical resistivity) is reasonable. Mahatsente et al () reported a positive Bouguer anomaly in the CMER (see Figure ), and Peccerillo et al (), Cornwell et al (), Mickus et al (), Lewi et al (), and others have interpreted such higher‐density bodies as crystallized gabbroic crustal magmatic intrusions. The 3‐D modeling of the gravity data by Mahatsente et al () included only one high‐density body swelling up from the upper mantle directly below Aluto but did not fit a second positive anomaly in their data further to the west that could be associated with the resistive Gademotta caldera.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous hours-to-days duration dike intrusions into the middle and upper crust have now been documented in magmatic segments over the last two decades (e.g., Grandin et al, 2011;Keir et al, 2011;Wright et al, 2006). A plethora of data from Ethiopia also indicate that the magmatic segments are underlain by seismically fast (e.g., Keranen et al, 2004;Mackenzie et al, 2005), dense (Cornwell et al, 2006;Lewi et al, 2016) crustal bodies, interpreted to be gabbroic intrusions, with little evidence for crustal thinning (Mackenzie et al, 2005;Maguire et al, 2006). In conjunction with studies of lithospheric mantle structure (e.g., Bastow et al, 2010;Kendall et al, 2006), geodetic data overall point toward a model of extension in which final plate separation occurs by melt intrusion and not ductile stretching (e.g., Bilham et al, 1999;Wright et al, 2006).…”
Section: Overviewmentioning
confidence: 99%